2011
DOI: 10.1016/j.polymdegradstab.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis and modelling of PET macromolecular changes during its mechanical recycling by extrusion

Abstract: The rheometer cavity has been chosen to analyze, in carefully controlled exposure conditions, the PET macromolecular changes generated during its mechanical recycling by extrusion. Isothermal ageing experiments at 280 C, under constant or variable oxygen partial pressures (between 0% and 21% of the atmospheric pressure), have allowed us to establish that two types of oxidative macromolecular changes take place successively in an extruder reactor. Chain scissions predominate in the "strongly oxygenated" zones (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 48 publications
4
109
0
8
Order By: Relevance
“…Their presence in small amounts in rPET-bg can significantly affect crystallinity during multiple extrusions. Some researchers have studied the degradation of rPET during processing and concluded that chain scission can occur and that formation of grafted copolymers and crystallization can be facilitated [4,5] and others concluded that during repetitive extrusion, chain scission predominated and no chain branching or cross-linking were observed which decreased capabilities and crystallinity [7,8], whereas others concluded that cross-linking and chain branching occur during extrusion [9,10]. This research study investigates the influence of thermo-mechanical degradation during repetitive extrusion cycles on the crystallinity of non-contaminated and contaminated rPET matrix with 5% PP.…”
Section: Introductionmentioning
confidence: 99%
“…Their presence in small amounts in rPET-bg can significantly affect crystallinity during multiple extrusions. Some researchers have studied the degradation of rPET during processing and concluded that chain scission can occur and that formation of grafted copolymers and crystallization can be facilitated [4,5] and others concluded that during repetitive extrusion, chain scission predominated and no chain branching or cross-linking were observed which decreased capabilities and crystallinity [7,8], whereas others concluded that cross-linking and chain branching occur during extrusion [9,10]. This research study investigates the influence of thermo-mechanical degradation during repetitive extrusion cycles on the crystallinity of non-contaminated and contaminated rPET matrix with 5% PP.…”
Section: Introductionmentioning
confidence: 99%
“…A titre d'information, les paramètres d'Arrhenius et les ordres de grandeur de k 3à 30 • C des principaux types de liaisons méthyléniques C-H sont donnés au Tableau 2. Ces valeurs sont issues d'études antérieures menées au laboratoire [3][4][5][6][7].…”
Section: Sites D'oxydationunclassified
“…Tout comme les polyesters [5] et les polyamides (PA) aliphatiques [6], les matrices EPO-DA vont donc subir une oxydation beaucoup plus sévère que le polyéthylène (PE …”
Section: Sites D'oxydationunclassified
See 2 more Smart Citations